TRANSFORMING BRAIN TUMOR DETECTION EMPOWERING MULTI-CLASS CLASSIFICATION WITH VISION TRANSFORMERS AND EFFICIENT NET V2 - Namratha S; Nageshwari (International Educational Journal of Science and Engineering, 2026)
Brain tumor detection is a crucial medical imaging task. In MRI images, accurate classification and detection of tumor sites in MRI play a crucial role in diagnosis and treatment success. In this study, we used the Brain Tumor MRI dataset for multi-class classification and detection. For classification we used advanced transfer learning models, such as EfficientNetV2, Vision Transformer ViT-B16, DenseNet121, and Xception. We also used ensemble averaging (average, weighted average, geometric mean) to improve prediction accuracy. We used several versions of YOLO (YOLOv5, YOLOv8, YOLOv9, and YOLOv11) with bounding box annotations in YOLO format to detect and localise tumors. We also applied explainable AI techniques such as Grad-CAM to generate heat maps of discriminative location of tumors that influence the model’s predictions. Our experimental results indicate that DenseNet121 and Xception-based models had the highest accuracy (99.54%) for the classification of tumors among all the classifiers. YOLO v8 had the best detection accuracy, with a Map of 95.1%. This shows that the combination of the classification and detection models with interpretability methods is a good approach to achieve a robust and accurate brain tumor diagnosis. We also developed a web app using Flask to use the models. This allows users to upload MRI images and get information about the tumor location, class, and confidence through a user-friendly interface.